Effect of mouthwashes with 0.05% sodium fluoride and 5% salt water on dental plaque and salivary pH. - Díaz Soriano, Ana María (2005)
The intention of this inuestigation consisted of evaluating the effects of two oral colutorios (colutorio with sodium fluoride to 0.05% and colutorio of water with salt to 5%) on fhe bacterial plate and salivary pH in a population of soldiers. The sample was conformed by three groups: a group use colutorio of sodium fluoride to 0.05%, another use colutorio of water with salt and third group control that used water distilled during 40 days. The characteristics of the population allowed to control important intervening variables such as the diet, buccal hygiene of the soldiers, moments of hygiene and fulfillment of the indicated protocol. PHmetro was used calibrated and the simplified index of Green and Vermillon, to measure salivary pH and the index of bacteria1 plaque, respectively. It was used the analysis of variance, and test T of student matched up samples and to establish differences. The results of the work of investigation as much indicated that colutorio with sodium fluoride to 0.05% as colutorio with water with salt to 5% behaves of similar way on the bacteria1 plate, diminishing it after 40 days; whereas no of the colutorios was able to alter salivary pH of significant form.